Use of wood ash as partial cement replacement in cement mortar - Pramod (My University, 2019)
Management of solid waste is the major concern globally due to increasing quantities of waste materials and by-products from industries. Lack of space availability for land filling and because of its increasing cost, utilization and recycling of industrial by-products and waste materials has the only option as it is economical and ecofriendly. There are several types of such materials, which can be recycled or reused in construction. The utilization of such materials in construction not only makes it economical, but also helps in reducing disposal problems. One such material is wood ash (WA). Wood ash (WA) is the residue generated due to combustion or incineration of wood and wood products (chips, saw dust, bark, etc.). The XRD (X-RAY DIFFRACTION) test results, SEM (scanning electron microscope) analysis and chemical analysis of WA showed that it contains amorphous silica and thus can be used as cement replacing material. Many researches had been carried out to incorporate wood waste ash as a cement replacement material in the production of greener construction material (concrete/mortar) and also as a sustainable means of disposal for wood waste ash. Results of these researches indicated that wood waste ash can be effectively used as a cement replacement material for the production of structural concrete/mortar of acceptable strength and durability parameters. This report presents an overview of the work carried out with cement mortar in which cement is partially replaced by wood waste ash on several aspects such as the physical, chemical, strength and durability properties of mortar with wood waste ash. This report shows the effect of wood ash on the workability, porosity, water absorption, compressive strength, flexural strength, thermal cycling, salt crystallization and rapid chloride permeability test etc.
Keywords: cement mortars; Thermal cycling; Salt crystallization